Comparative Evaluation of OpenFOAM® and ANSYS® Fluent for the Modeling of Annular Reactors. Issue 7 (12th June 2018) - Ariza, Cristian; Casado, Cintia; Wang, Ruo-Qian; Adams, Eric; Marugán, Javier
Abstract: A three‐dimensional numerical model was solved for a turbulent incompressible steady flow and the discrepancies and similarities between the software OpenFOAM® and ANSYS® Fluent on the flow modeling were analyzed. The evaluation was performed for the meshing, setup, and simulation step of the modeling process. Outcomes were contrasted with experimental data to validate the fluid flow obtained with both softwares. With this aim, an experimental pulse‐response technique was applied to obtain the residence time distribution (RTD) curve to be compared with the RTD curves achieved from the modeling. Additionally, images of the tracer transport in the experimental reactor were taken, showing good agreement with the computational fluid dynamics (CFD) predictions. Abstract : The differences and similarities between the softwares OpenFOAM® and ANSYS® Fluent on flow modeling were analyzed and a 3D numerical model was solved for a turbulent incompressible steady flow. The fluid mechanics and mass transport model predictions of both softwares were evaluated in order to make the simulation models as comparable as possible. Results were contrasted with experimental data.